Clinicopathological characteristics of SMAD4 gene expressions in colorectal cancer patients: SMAD4 gene and colorectal cancer - Mansouri, Neda; Mozooni, Zahra; Haghighi, Mehrdad; Soleimani, Shahrzad; Ghadyani, Rezvan; Parsazad, Ehsan; Azari, Sepideh; Rezaei Tavirani, Mostafa; Kahrizi, Sepehr; Rouhollahpour Ahangar, Ehsan; Movafagh, Abolfazl (Cellular and Molecular Biology, 2024)
Colorectal cancer (CRC) ranks as the third leading cause of cancer-related deaths globally. SMAD4 gene acts as the central mediator of the signaling pathway for transforming growth factor-β (TGFβ) with a significant effect on colorectal cancer. Previous research has confirmed a relationship between the presence of the SMAD4 gene and the survival and progression of colorectal cancer in patients. In this study, our goal was to analyze the presence of SMAD4 in both colorectal cancer and nearby normal tissues. The expression levels of SMAD4 were evaluated in 45 colorectal tumor tissues and 45 adjacent control tissues using the Quantitative Real-Time PCR (qRT-PCR) method. Additionally, we assessed the diagnostic effectiveness of SMAD4 by creating a receiver operating characteristic (ROC) curve. Our findings showed that the expression of SMAD4 was significantly reduced in colorectal cancer patients compared to the adjacent control group sample. Examination of clinicopathological characteristics of patients revealed varied correlations between SMAD4 gene expressions and TMN stage (p<0.0001). These findings suggest that SMAD4 levels could be used as possible diagnostic indicators for colorectal cancer.